2017
DOI: 10.18433/j37w7r
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Reverses Induced Expression of Efflux Proteins and Potentiates Cytotoxic Activity of Gemcitabine in Capan-2 Pancreatic Cancer Cells

Abstract: ABSTRACT-Purpose. Efflux and influx proteins play a major role in chemo-resistance by affecting the net cellular uptake of anti-cancer drugs. Hence, alteration of the efflux and influx protein expression may result in variations of chemotherapeutics uptake and consequently cell death rate. The present study investigated the effects of pre-treatment of capan-2 pancreatic cancer cells with calcitriol, butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA) or silibinin on the induction of three major effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Vitamin D has been found to have antitumour effects, suggesting that it might inhibit the progression of rectal cancer 10 , breast cancer 11 , pancreatic cancer 12,13 , head and neck cancers 14 and other cancers. Urashima 15 suggested that the higher the serum level of vitamin D is, the better is the prognosis of rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been found to have antitumour effects, suggesting that it might inhibit the progression of rectal cancer 10 , breast cancer 11 , pancreatic cancer 12,13 , head and neck cancers 14 and other cancers. Urashima 15 suggested that the higher the serum level of vitamin D is, the better is the prognosis of rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Capan-2 pancreatic cancer cells were pretreated with BHT, BHA, calcitriol, or silibinin for 24 h, and then treated with gemcitabine [ 89 ]. BHT, BHA and silibinin all up-regulated the expression levels of efflux proteins and decreased gemcitabine uptake, while calcitriol strongly suppressed the expression of efflux proteins, and increased gemcitabine uptake.…”
Section: Silymarin and Gastrointestinal Cancermentioning
confidence: 99%
“…Pre-treatment with calcitriol protected the cells against gemcitabine toxicity, while BHA increased the cell death rate. Neither BHT nor silibinin had any significant effect on the cell death rate [ 89 ].…”
Section: Silymarin and Gastrointestinal Cancermentioning
confidence: 99%
“…Combining chemotherapy with vitamin D has been under consideration for several years. Overall, the results of such combination treatments have been consistently beneficial [ 214 , 215 , 216 , 217 ]. This conclusion was verified and extended in an experiment on a mouse model, showing that supplementing gemcitabine with calcipotriol (a synthetic derivative of vitamin D) significantly increased median survival by some 50% ( Figure 9 B) [ 218 ].…”
Section: Dietary Considerationsmentioning
confidence: 99%